Bridging the divide in financial market forecasting: machine learners vs. financial economists. (1st November 2016) - Hsu, Ming-Wei; Lessmann, Stefan; Sung, Ming-Chien; Ma, Tiejun; Johnson, Johnnie E.V.
Highlights: An extensive benchmark in financial time series forecasting is performed. Best machine learning(ML) methods out-perform best econometric methods. The ML methodology employed significantly affects forecasting accuracy. Market maturity, forecast horizon & model-assessment method affect forecast accuracy. Evidence against the informational value of technical indicators. Abstract: Financial time series forecasting is a popular application of machine learning methods. Previous studies report that advanced forecasting methods predict price changes in financial markets with high accuracy and that profit can be made trading on these predictions. However, financial economists point to the informational efficiency of financial markets, which questions price predictability and opportunities for profitable trading. The objective of the paper is to resolve this contradiction. To this end, we undertake an extensive forecasting simulation, based on data from thirty-four financial indices over six years. These simulations confirm that the best machine learning methods produce more accurate forecasts than the best econometric methods. We also examine the methodological factors that impact the predictive accuracy of machine learning forecasting experiments. The results suggest that the predictability of a financial market and the feasibility of profitable model-based trading are significantly influenced by the maturity of the market, the forecasting method employed, the horizon for which it generates predictions and the methodology used to assess the model and simulate model-based trading. We also find evidence against the informational value of indicators from the field of technical analysis. Overall, we confirm that advanced forecasting methods can be used to predict price changes in some financial markets and we discuss whether these results question the prevailing view in the financial economics literature that financial markets are efficient.